Influence of late pruning practice on two red skin grapevine cultivars in a semi-desert climate - Perin, Corrado; Verma, Pankaj Kumar; Harari, Gil; Suued, Yedidya; Harel, Matanya; Ferman-Mintz, Danielle; Drori, Elyashiv; Netzer, Yishai; Fait, Aaron (Frontiers in Plant Science, 2023)
Continually increasing global temperature could severely affect grape berry metabolite accumulation and ultimately wine polyphenol concentration and color intensity. To explore the effect of late winter shoot pruning on grape berry and wine metabolite composition, field trials were carried out on Vitis vinifera cv. Malbec and cv. Syrah grafted on 110 Richter rootstock. Fifty-one metabolites were detected and unequivocally annotated employing UPLC-MS based metabolite profiling. Integrating the data using hierarchical clustering showed a significant effect of late pruning treatments on must and wine metabolites. Syrah metabolite profiles were characterized by a general trend of higher metabolite content in the late winter pruning treatments, while Malbec profiles did not show a consistent trend. In summary, late winter shoot pruning exerts a significant effect, though varietal specific, on must and wine quality-related metabolites, possibly related to enhanced photosynthetic efficiency, which should be taken into consideration when planning mitigating strategies in warm climates.